Biochemical Characterization of PECAM-1 (CD31 Antigen) on Human Platelets - Metzelaar, Marcel J; Korteweg, Jeanne; Sixma, Jan J; Nieuwenhuis, H Karel (Thrombosis and Haemostasis, 1991)
The platelet plasma membrane expresses several membrane glycoproteins with a high molecular weight. In this study we have investigated the properties of the CD31 antigen on platelets and endothelial cells using the monoclonal antibody (MoAb) RUU-PL 7E8. Comparative studies revealed that the CD31 antigen, PECAM-1 and endoCAM are the same protein. The CD31 antigen was immunoprecipitated with a molecular mass of 125 kDa nonreduced and 135 kDa reduced from Nonidet-P40 lysates of surface labeled human platelets. The relative position in two-dimensional nonreduced/reduced SDS-PAGE and IEF-PAGE, compared to other glycoproteins of similar molecular weight, was elucidated. The position of the CD31 antigen was clearly distinct from the position of the platelet membrane glycoproteins Ia, Ib, IIa, IIb, IIIa and the granule membrane protein GMP-140. Native resting platelets bound 7,760 ± 1,670 molecules/platelet, whereas thrombin-stimulated platelets bound 14,500 ± 3,790 molecules/platelet. Immunoelectron microscopy revealed the presence of the CD31 antigen on the membrane of both resting and thrombin-activated platelets. Immunofluorescence studies showed the presence of the CD31 antigen in the membrane of endothelial cells on sites of cell-cell contact, suggesting that the CD31 antigen might be involved in cell-cell interaction. In functional studies, MoAb RUU-PL 7E8 did not inhibit platelet aggregation, platelet adherence to the extracellular matrix of endothelial cells and purified collagen fibrils under flow conditions, nor was any influence found on endothelial cell detachment and growth.